Efficient Use Of «Solving Tasks’ Environment» In Distance Learning System «Web-Almir» Duiring Studying Linear Algebra (Journal of Information Technologies in Education (ITE), 2009)
We analyzed question of linear algebra studying as one of fundamental chapter in mathematics. We propose to study material by using “Solving tasks’ environment”.
Keywords: information and communication technology; linear algebra; «Web-Almir»; “Environment for the solving tasks”; “Expert”